Legal Study of the Appointment of Regional Head Officials from TNI/Polri Officials - Nasrin, Nasrin; aibu, Rahmat T; Hamid, La Ode Abdul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to find out the legal rules related to the appointment of Acting Regional Heads from TNI/POLRI High Officers. The proposal to appoint active high-ranking TNI/PORI officers as Acting Regional Heads by the Ministry of Home Affairs has drawn polemics. The method used in this research is qualitative research through a normative legal approach, namely an approach that uses positivist juridical conceptions. The data collected is by using literature studies, scientific articles, legal expert opinions, and other legal sources. The data that has been obtained is then analyzed using qualitative analysis methods. Based on the research results obtained in this study, the following conclusions were drawn: (1) The appointment of Acting Regional Heads from TNI/POLRI elements is contrary to Article 109 Paragraph 2 of Law Number 5 of 2014 concerning State Civil Apparatus, which states